Functional Analysis of Oil Palm Metallothionein-Like Gene Promoter (MT3-A) in Bacteria and Transgenic Tomato - Kamaladini, Hossein (2011)
Reporter gene activity under the regulation of the oil palm metallothionein-like gene promoter (MT3-A) was assessed in prokaryotes and transgenic tomato. Vector constructs containing MT3-A promoter with (W1MT3-A) and without (W2MT3-A) five prime untranslated region (5'-UTR) fused to ß-glucuronidase (GUS) gene in pCAMBIA 1304 vector were produced. Competitive RT-PCR and GUS fluorometric assay showed changes in the level of GUS gene transcripts and enzyme activity in response to increasing concentrations of Cu2+ and Zn2+ in E. coli and A. tumefaciens. In E. coli, a high level of GUS activity driven by W1MT3-A and W2MT3-A was observed in treatment with 25μM Cu2+ resulting in an increase in the GUS mRNA level to 7.2 and 7.5 x 10-4 pmole/μL respectively, compared to the control (without Cu2+) at 5.1 x 10-4 pmole/μL. The application of different Zn2+ concentrations resulted in a strong decrease in the GUS activity and GUS mRNA level in E. coli and A. tumefaciens. The results of Agrobacterium-mediated transformation of tomato showed that MS medium containing 2 mg/L zeatin, 6 mg/L hygromycin and 300 mg/L of timentin was optimum to acquire the maximum putative shoot regeneration of tomato var. MT1. Histochemical GUS assay analysis of different tissues of transgenic tomato showed that W1MT3-A or the W2MT3-A only drove GUS expression in the reproductive tissues and organs, including the stamen, fruit as well as the seed coat compared to the controls. Based on the standard curves the concentrations of GUS cDNA driven by W1MT3-A and W2MT3-A fragments in fruits of independent lines of transgenic tomato (containing one copy number) were calculated to be 9.9 x 10-4 and 8.3 x 10-4 pmole/μL, respectively. In transgenic tomato fruits harboring the W1MT3-A, the highest level of GUS activity was observed (13.5-fold) in the independent line containing three copy number compared to the control (untransformed fruit). In the leaves of L1W1MT3-A seedlings, the highest and the lowest GUS activity was observed at 150 μM and 50 μM Cu2+, respectively compared to the control without Cu2+. Results of the Zn2+ and Fe2+application showed no increase in GUS activity driven by the MT3-A promoter in the leaves of L1W1MT3-A seedlings compared to the control. The highest level of GUS activity driven by W1MT3-A was observed in treatments with 100 μM ABA (4-fold), compared to the absence of ABA as control. In addition, the leaves of the L1W1MT-A seedlings under 14 days drought stress showed an increase (11.6-fold) in GUS activity compared to the untreated L1W1MT3-A seedlings as control. This is the first report that showed the oil palm MT3-A promoter is functional in prokaryotes and produced detectable GUS transcripts and enzyme activities. Furthermore, it showed that the MT3-A promoter is a tissue specific promoter in transgenic tomato and can be induced by abiotic stress such as drought and ABA or metal ions like Cu2+. Stressinducible activity of the oil palm MT3-A promoter may potentially be used in prokaryotic, monocot and dicot plants in genetic engineering for improving their metabolism, nutritional value and production of novel products.